Potentials of seedling growth parameters as selection indices in Tetrapleura tetraptera (Schum & Thonn) Taub. from Southwestern Nigeria (2005)
The study investigated variations among progenies of Tetrapleura teraptera (Schum & Tbonn) (Taub.) from four sources in South Western Nigeria with a view to identifying early growth traits that could be useful for the selection of superior genotypes for breeding and improvement of the species. The three seed sources include: Emure-Ekiti (Latitude 702 26’ N and Longitude 502 30’ E); Ikoji-Ile (Latitude 80 15’N and Longitude 402 49’ E); Osogbo (Latitude 702 46’N and Longitude 402 35’ E) and Sapele (Latitude 502 55’N and Longitude502 46’E). Seedlings used for the experiment were part of those produced from an earlier germination experiment carried out in the nursery of the Department of Forest Resources Management, University of Ibadan. After the germination experiment, 32 uniformly growing and vigorous seedlings were pricked out from each progeny into medium sige polypots (25 cm x 14.5 cm x 7.5 cm). At fortnightly intervals, four seedlings were selected from each progeny for study. On each occasion, seedling height, collar diameter, number of leaves and total dry weights were assessed. Net Assimilation rates and Relative Growth Rates were calculated on each occasion. The study lasted for 12 weeks. The data generated were subjected to Analysis of Variance and the least significant difference was calculated to separate significantly different means. Results indicate highly significant variations in seedling heights, collar diameter and Relative Growth Rates among the 4 progenies. Ikoyi- ile progeny had the highest mean values of seedling height (12.9 cm) mean diameter (1.4 cm); mean number of leaves (15.6) and Relative Growth Rate (0.239grnf m2 / wk). Osogbo progeny recorded the least mean values for height (10.3 cm) mean collar diameter (1.3 cm), mean number of leaves (13.6) and total dry weight (0.123 gm). The effect of age was highly significant on all the parameters measured. This is an indication that reasonable variations occur within the population of T. tetraptera in the study area. It is recommended that genetic investigations be carried out on this species to corroborate the observations made in this study.